Validation of the videogame consumption habits questionnaire in Chilean millennials (2020)
The massification of the use of video games has been growing rapidly and in addition the projections suggest that use will continue to increase over time. For the measurement of video game consumption there are numerous questionnaires, which are mostly associated with the diagnosis of psychological disorders. As the objective is to measure the use and consumption of videogames and not the diagnosis of psychological disorders, it was decided to validate the questionnaire of habits of videogames consumption, originally created for the Spanish population. For this reason, a confirmatory factor analysis was carried out for the Chilean millennial population, who are people born between 1980 and 2000. For the validation, a sample composed of 412 university students was used. Reliability and validity were calculated. This was measured with the composite reliability coefficient, mean variance extracted and Cronbach's ?. The maximum likelihood estimate with the robust Satorra-Bentler correction. The results obtained to validate the scale show that it is valid and reliable for use in young Chileans belonging to the millennial generation or generation Y.